Advanced chemical science-based high-resolution low-cost printing for high performance printed electronics - Shi, Jingsheng (2012)
Printing processes are promising alternatives to photolithography for printed electronics. It is essential to applications such as large-area flat-panel displays, electronic paper, radio frequency identification tags (RFID tags), and ultraportable disposable sensors, which have requirements other than operating speeds and increasingly complicated circuits for better manufacturability. The impact of printing processes on device performance is still underexplored. Understanding and advancing the chemical sciences involved in printing electronics is essential to develop new printing technologies or improve existing printing processes for high performance organic semiconductor/CNT- based printed electronics.